2006
DOI: 10.1111/j.1540-5885.2006.00186.x
|View full text |Cite
|
Sign up to set email alerts
|

PERSPECTIVE: Establishing an NPD Best Practices Framework

Abstract: Achieving NPD best practices is a top-of-mind issue for many new product development (NPD) managers and is often an overarching implicit, if not explicit, goal.The question is what does one mean when talking about NPD best practices? And how does a manager move toward achieving these?This article proposes a best practices framework as a starting point for muchneeded discussion on this topic. Originally presented during the 2004 Product Development Management Association (PDMA) Research Conference in Chicago, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
162
3
29

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 178 publications
(196 citation statements)
references
References 15 publications
2
162
3
29
Order By: Relevance
“…Providing the real product advantages that customers are demanding remains a challenge, despite the acknowledgement that early identification of customers' future needs is a vital stage of new product development (Griffin, 1997;Kahn et al, 2006;Williams and Kochhar, 2000). This may be partly explained by the changing relationship between producers and customers.…”
Section: The Need For Customer Knowledge In New Product Developmentmentioning
confidence: 99%
“…Providing the real product advantages that customers are demanding remains a challenge, despite the acknowledgement that early identification of customers' future needs is a vital stage of new product development (Griffin, 1997;Kahn et al, 2006;Williams and Kochhar, 2000). This may be partly explained by the changing relationship between producers and customers.…”
Section: The Need For Customer Knowledge In New Product Developmentmentioning
confidence: 99%
“…Since the 1980's numerous benchmarking studies have been conducted to identify best practice and common factors evident in successful companies. It has consistently been found that the extent to which customer research is used and integrated within an NPI process, together with a process that is firmly implemented, are two of the strongest discriminators between best and worst performing businesses (Cooper, Edgett, and Kleinschmidt, 2004, Cooper and Kleinschmidt, 1991, Griffin, 1997, Kahn, Barczak and Moss, 2006.…”
Section: The Changing Nature Of Customer Research In New Product Intrmentioning
confidence: 99%
“…O estabelecimento de estratégias específicas para o PDP tem um impacto positivo no sucesso do novo produto, pois direciona os esforços e cria uma visão compartilhada pelos membros da equipe de desenvolvimento (COOPER et al, 2004b;GRIFFIN;KAHN, 2009 GARRET, 1997;ERNST, 2002;COOPER et al, 2004c;MOSS, 2006).…”
Section: Fatores Críticos De Sucesso No Pré-desenvolvimentounclassified
“…Pesquisadores e profissionais de empresas têm dado mais atenção às atividades do pré-desenvolvimento devido a seu impacto na qualidade, no tempo de conclusão do projeto e nos custos de desenvolvimento. Diversos autores discutiram a importância do pré-desenvolvimento para o sucesso dos novos produtos (COOPER; KLEINSCHMIDT, 1995;GRIFIN, 1997;WILEMON, 2002;ERNST, 2002;COOPER et al, 2004c; KAHN; BARCZAK; MOSS, 2006;BACKMAN;BORJESSON;STEN, 2007;WERWORN;HERSTATT;NAGAHIRA, 2008).…”
Section: Introductionunclassified